CREATIVITY AND INNOVATION IN THE XXI CENTURY SCHOOL: A PARADIGM SHIFT - Kênia Paulino de Queiroz Souza; Maria José de Pinho (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
This article aims to make known the main concepts of creativity and innovation in contemporary school, with the breakup of the conservative paradigm for emancipatory education, and discuss this break, which operates a change in educational institutions according to the conceptions and theoretical references on the create and innovate, in "vision of transformation". The study, of bibliographical character, began with the analysis of the theoretical in the "International Network Research Group Investigating creative and innovative Schools", which led to the perception that the contemporary school, to oppose a conservative education, which prioritizes the individual work and fragmented knowledge, can be defined as emancipatory, creative and innovative, because it has the vision and transformative forming of your do and pedagogical collective , and search the interconnection of knowledge and the production of knowledge. The creative potential, nature and the human being are valued, aiming at the individual, social and planetary good, according to principles that depart from and for life.